MAJOR PATHWAYS OF ENDOTHELIAL DYSFUNCTION UNDER EXPERIMENTAL MILD HYPOTHYROSIS - Chupashko, O.I. (World of Medicine and Biology, 2015)
Present research demonstrates metabolic correlation between mild hypothyrosis and endothelial dysfunction (ED). The subclinical hypothyrosis is associated with increased serum levels of LDL and reduced HDL, and finally, with increased atherogenic index (0,530 ± 0,035), that can be interpreted as atherogenic dyslipidemia, which largely contributes to ED. Parameters of nitric oxide system showed decrease in nitrite-ion concentration in rat blood. It can predict the tendency to endothelial dysfunction in SH. According to our research, thyroid function is significantly related to the changes of free-radical component of metabolism. We found the activation of lipoperoxidation (LPO) processes in blood, and, moreover, the antioxidant enzymes activity was to the contrary depressed under mild thyroid failure. Intermittent hypoxic training (IHT) was tested with a purpose to correct the biochemical abnormalities and showed positive effects, in fact, in regard to all investigated parameters.